2016
DOI: 10.1093/ajh/hpw030
|View full text |Cite
|
Sign up to set email alerts
|

Diuretics for Hypertension: A Review and Update

Abstract: This review and update focuses on the clinical features of hydrochlorothiazide (HCTZ), the thiazide-like agents chlorthalidone (CTDN) and indapamide (INDAP), potassium-sparing ENaC inhibitors and aldosterone receptor antagonists, and loop diuretics. Diuretics are the second most commonly prescribed class of antihypertensive medication, and thiazide-related diuretics have increased at a rate greater than that of antihypertensive medications as a whole. The latest hypertension guidelines have underscored the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
120
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(141 citation statements)
references
References 60 publications
2
120
1
8
Order By: Relevance
“…25 Chlorthalidone only accounted for 3% of prescriptions in patients with resistant hypertension, who may need a more potent diuretic. 26 It is an open question, however, if hydrochlorothiazide has the same cardiovascular benefit as chlorthalidone.…”
Section: Hypertensionmentioning
confidence: 99%
“…25 Chlorthalidone only accounted for 3% of prescriptions in patients with resistant hypertension, who may need a more potent diuretic. 26 It is an open question, however, if hydrochlorothiazide has the same cardiovascular benefit as chlorthalidone.…”
Section: Hypertensionmentioning
confidence: 99%
“…Interestingly, in a small, short-term (12-week) mechanistic study in T2D patients (19), treatment with dapagliflozin (another selective SGLT2 inhibitor) resulted in a smaller reduction in blood pressure than did treatment with a comparator diuretic (25 mg hydrochlorothiazide), but also in a 7% decrease in plasma volume (as directly measured with the use of 125 I-labeled albumin) and some increment in N-terminal pro-BNP levels, neither of which were observed with the treatment with the diuretic agent. Thiazide diuretic agents decrease plasma volume only transiently, whereas in the EMPA-REG OUTCOME trial the observed increase in hematocrit persisted for the entire duration of the trial (20).…”
mentioning
confidence: 92%
“…RAPL is an antihypertensive drug and HCTZ is a diuretics drug, both of which are used in the treatment of high blood pressure (de Leeuw and Birkenhäger 1987;Roush and Sica 2016). At 0.8% (w/v), dendrimer concentration the RAPL solubility was increased 4.91-fold with amine-terminated dendrimer, whilst the optimal dendrimer for HCTZ solubilisation (3.72-fold) was with carboxy-terminated functional groups.…”
Section: Dendrimersmentioning
confidence: 99%